Technical efficiency and productivity growth of crude palm oil: Variation across years, locations, and firm sizes in Indonesia - Haura Azzahra Tarbiyah Islamiya; Dyah Wulan Sari; Mohammad Zeqi Yasin; Wenny Restikasari; Mohd Shahidan Shaari; Mochamad Devis Susandika (Economies, 2022)
Crude palm oil (CPO) is a valuable commodity for Indonesia's economy as the country has become the world's biggest producer and exporter. Therefore, maintaining productivity in the CPO industry is crucial to ensure that the global demand is met. This study aims to examine Indonesian CPO productivity and its components using total factor productivity growth (TFPg) with stochastic frontier analysis. This study analyzes the variation in the TFPg across years, locations, and firm sizes. The first two analyses imply that, on average, the CPO industry's productivity declines annually, with firms in 20 provinces experiencing negative TFPg. Regarding size, the analysis demonstrates that the technical efficiency change (TEC) and technical change (TC) have regressed the TFPg in all scale firms. However, medium firms saw a smaller decline in comparison to large firms. Conversely, large firms possess slightly better scale efficiency change (SEC) than medium firms, although both types attain a negative SEC. The findings also show that the main factor contributing to the gain or decline in productivity is TC, which suggests the urgency of innovative technology in the CPO industry.
Keywords: 330; crude palm oil; firm size; technical efficiency; total factor productivity growth